Intestinal Flora Disruption and Novel Biomarkers Associated With Nasopharyngeal Carcinoma - Jiang, Haiye; Li, Jian; Zhang, Bin; Huang, Rong; Zhang, Junhua; Chen, Ziwei; Shang, Xueling; Li, Xisheng; Nie, Xinmin (Frontiers in Oncology, 2019)
Background Nasopharyngeal carcinoma (NPC) is a malignant nasopharyngeal disease with a complicated etiology that occurs mostly in southern China. Intestinal flora imbalance is believed to be associated with a variety of organ malignancies. Currently, the relationship between intestinal flora and NPC is not clear, although many studies have shown that intestinal flora can be used as a biomarker for many cancers and to predict cancer. Methods To compare the differences in intestinal flora compositions and biological functions among 8 patients with familial NPC (NPC_F), 24 patients with sporadic NPC (NPC_S) and 27 healthy controls (NOR), we compared the intestinal flora DNA sequencing and hematological testing results between every two groups using bioinformatic methods. Results Compared to the NOR group, the intestinal flora structures of the patients in the NPC_F and NPC_S groups showed significant changes. In NPC_F, Clostridium ramosum, Citrobacter spp., Veillonella spp. and Prevotella spp. were significantly increased, and Akkermansia muciniphila and Roseburia spp. were significantly reduced. In NPC_S, Clostridium ramosum, Veillonella parvula, Veillonella dispar and Klebsiella spp. were significantly increased, and Bifidobacterium adolescentis was significantly reduced. A beta diversity analysis showed significant difference compared NPC_F with NOR based on Bray Curtis(P=0.012) and Unweighted UniFrac(P=0.0045) index, respectively. The areas under the ROC curves plotted were all 1. Additionally, the concentrations of 5-HT in NPC_F and NPC_S were significantly higher than those of NOR. C. ramosum was positively correlated with 5-hydroxytryptamine(5-HT) (rcm: 0.85, P<0.001). A functional analysis of the intestinal flora showed that NPC_F was associated with Neurodegenerative Diseases (P=0.023), Biosynthesis of Other Secondary Metabolites (P=0.038) and that NPC_S was associated with Neurodegenerative Diseases (P=0.045). Conclusion We, for the first time, found that NPC was associated with structural imbalances in the intestinal flora, with Clostridium ramosum that promoted the elevation of 5-HT and opportunistic pathogens being significantly increased, while probiotics significantly decreased. C. ramosum can be used as a novel biomarker and disease prediction models can be established for NPC. The new biomarker and disease prediction models can be used for disease risk prediction and the screening of high-risk populations, as well as for the early noninvasive diagnosis of NPC.